THE ANALYSIS OF INTENTION TO BUY BOOKS BETWEEN REGULAR STUDENTS AND IBA STUDENTS OF FACULTY OF ECONOMICS AND BUSINESS SAM RATULANGI UNIVERSITY - Lelengboto, Jeane Elisabeth (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The study of Consumer Behavior has become essential. Consumer buying behavior has become an integral part of strategic market planning. Book is one of the most essentials part in learning process and activities. The purposes of this research are to analyze the difference of intention to buy books between International Business Administration (IBA) students and Regular students. The method that used in this research is Independent Sample t-test. Independent Sample t-test is a method to compares the mean score of two groups on given variable. Independent sample t-test method is used to analyze the data in this research. Data analysis in this research shows the independent sample t-test result between the group of International Business Administration student and Regular student. Theories supporting this research are marketing, consumer behavior, consumer buying behavior, and purchase intention. The population and sample observed in this research are 100 respondents; consist of 50 respondents by International Business Administration (IBA) and 50 respondents by Regular student of Faculty of Economy and Business Sam Ratulangi University. The result from the study is Consumer Buying Behavior and Purchase Intention of academic books towards International Business Administration (IBA) students and Regular students Faculty of Economics and Business Sam Ratulangi University have a different significant of each factor from academic books. Keywords: consumer buying behavior, purchase intention.